The patterns of nitrogen and phosphorus stoichiometry across communities along altitudinal gradients in Qilian Mountains, China. (October 2015) - Xu, Shi-Jian; Fan, Xiao-Yong; Wang, Li-Long; Zhang, Xin-Fang; An, Li-Zhe
Abstract: Unraveling the distribution patterns of plant nitrogen (N), phosphorus (P) stoichiometry along the elevational gradients has been attracting growing scientific interests of ecologists. However, little is known about patterns of plant root N, P stoichiometry along elevation and the relationship between foliar and root. Here we determined the foliar and root N, P concentrations and clarified the patterns of N:P stoichiometry across functional groups and community types along a 2000 m altitudinal gradient in Qilian Mountains, China. Generally, foliar N remained constant but P increased, therefore foliar N:P ratio decreased against elevation. Foliar N, P and N:P were different considerably and correlated highly with that in root, respectively. One-way ANOVA demonstrated stable root N content across the communities, and remarkably higher root P at the higher rather than at the lower sites. For the foliar, the alpine bushwood had the lowest foliar P, but highest N content, whereas the alpine cold-desert presented the lowest foliar N, but higher P concentration. The well-constrained N:P ratios indicated no significant limitation in N or P in the study area. These results together suggest that plant foliar N, P contents do not simply increase with elevation, and the vegetation type, specifically at the arid and low temperature environments, may play crucial roles on patterns of plant N:P stoichiometry at alpine region. Highlights: Plant foliar and root N, P stoichiometric patterns along altitudinal gradients were addressed. The foliar N was constant and P increased with elevation. Foliar N, P and N:P were different and correlated with that of roots. The foliar N, P stoichiometric patterns may be associated with vegetation types. N:P ratios were constrained across communities.